The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/6667011
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Expression of Vascular Endothelial Growth Factor and the Potential Effect of Promoting Hair Growth Treated with Chinese Herbal BeauTop

Abstract: Despite minoxidil and finasteride already being approved by the Food and Drug Administration (FDA) for the treatment of hair loss, it is important to identify new and innovative treatments for hair loss, such as looking for a solution in Chinese herbal medicine. One such treatment to consider is BeauTop (BT), whose primary ingredients include Panax japonicus (T.Nees), C.A. Mey. (Araliaceae), Astragalus membranaceus (Fisch) Bunge (Fabaceae), Angelica sinensis (Oliv.) Diels (Apiaceae), Ligustrum lucidum W.T. Ait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It is important to emphasize the capacity of alopecia treatments to promote the transition from the telogen phase to the anagen phase, a critical stage in the hair growth cycle. Several studies have demonstrated that this transition is regulated by several proteins released by hair follicle cells, including growth factors, which work synergistically to stimulate the proliferation of hair follicle cells and facilitate hair growth during the anagen phase [13][14][15][16][17][18][19][20][21][22][23][24][25]34,[42][43][44][45][46]. FGF-7, also known as HGF, is a growth factor released by dermal papilla cells, dermal cells, and to a lesser extent, epidermal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize the capacity of alopecia treatments to promote the transition from the telogen phase to the anagen phase, a critical stage in the hair growth cycle. Several studies have demonstrated that this transition is regulated by several proteins released by hair follicle cells, including growth factors, which work synergistically to stimulate the proliferation of hair follicle cells and facilitate hair growth during the anagen phase [13][14][15][16][17][18][19][20][21][22][23][24][25]34,[42][43][44][45][46]. FGF-7, also known as HGF, is a growth factor released by dermal papilla cells, dermal cells, and to a lesser extent, epidermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that plant extracts can stimulate hair growth by activating the cell cycle and increasing the expression and activation of various growth factors, such 2 of 19 as epidermal growth factor (EGF), fibroblast growth factor 7 and 2 (FGF 7-2), vascular endothelial growth factor (VEGF), keratinocyte growth factor (KGF), insulin-like growth factor 1 (IGF), and hepatocyte growth factor (HGF) [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Perifollicular vascularization is extensively active in the anagen phase and correlated with the upregulation of VEGF in follicular keratinocytes, leading to the acceleration of hair regrowth [ 61 ]. The size of hair follicles and the diameter of the hair shaft were also increased due to VEGF [ 62 ]. In addition, the mechanisms of minoxidil involved the upregulation of VEGF and its receptor in hHFDPC, leading to the promotion of angiogenesis in the anagen phase [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In research on the effects of Chinese herbal extracts on hair growth, certain Chinese medicines, such as ginseng, red ginseng oil, and Platycladus orientalis , have been demonstrated to exert positive effects on hair growth (Choi, 2018; Truong et al, 2017; Zhang et al, 2016). For example, Chinese herbal medicine BeauTop, the main ingredients including Panax japonicus (T.Nees), can promote hair growth by boosting the expression of VEGF in hair follicles in C57BL/6Jmice (Lee et al, 2021). Jung et al reported that Mangifera Indica leaf extracts promote hair growth via activation of Wnt signaling pathway in human dermal papilla cells (Jung et al, 2022).…”
Section: Introductionmentioning
confidence: 99%